Review of the grassland leafhopper subgenus Leofa (Prasutagus) Distant (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) - Duan, Yani; Zhang, Yalin; Webb, M. D. (Zootaxa, 2009)
The grassland leafhopper subgenus Leofa (Prasutagus) is reviewed. Five species are dealt with in this paper, including two new species from China: Leofa (Prasutagus) forcipatus Duan & Zhang sp. nov. and Leofa (Prasutagus) yangae Duan & Zhang sp. nov., and a key to species is provided.